ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA UMKM (Studi Empiris pada UMKN di Kota Malang) - Muhammad Aditya Kurniawan; Abdul Wahid Mahsuni; Hariri Hariri (Universitas Islam Malang, 2020)
ABSTRACT Accounting information is required for managers or company owners to carry out company activities. Encourage accounting knowledge to study in the field of corporate accounting. Accounting information is required for managers or company owners to carry out company activities. Motivation to learn accounting information deepens the understanding of managers or owners in corporate accounting practices. In addition, sales figures have a significant impact on the use of accounting in your business. The smaller the sales, the harder it is to find your accounting and financial statements. Accounting information has a large impact on business success, including small businesses. This study seeks to study the factors that influence the use of accounting information at MSMEs. The independent variables used in this study are education level, educational background, lead time, business scale, and accounting knowledge, while the dependent variable in this study is the use of accounting information. The respondents in this study were 84 respondents. Based on the test results that simultaneously variable levels of education, educational background, business scale, time to lead the company and accounting knowledge simultaneously have a significant effect on the use of accounting information. Partially the education level variable has no effect on the use of accounting information, the educational background variable has a significant positive effect on the use of accounting information, the lead time variable of the company has no effect on the use of accounting information, the business scale variable has no effect on the use of accounting information, the accounting knowledge variable has a positive effect and significant to the use of accounting information.Keywords: education level, educational background, leadership period, business scale, accounting knowledge and use of accounting.